If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 + y = 72 Solving 65 + y = 72 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + y = 72 + -65 Combine like terms: 65 + -65 = 0 0 + y = 72 + -65 y = 72 + -65 Combine like terms: 72 + -65 = 7 y = 7 Simplifying y = 7
| -7(m+3)=2(12-6m) | | .15x+.05(2-x)=.10(17) | | 150s(225s-3.50)=2000 | | -2+3x=-5 | | 0=25a+2 | | 4a-5b=6b | | (2x-9)+(3x^2-5x+3)=x | | 9x+29-x-28=87 | | -1+5x=39 | | (6n-4)+14=1 | | .24(10000)-.02y=.08(y+10000) | | -15-15x=-4x-8x | | 5x-15=25y | | 2(X+4)+2=4 | | -(3x-1)= | | 2(2x-2)=-16 | | 9-2(x-3)=9 | | 5x+5(3x-7)=125 | | .30(24)+.05x=.15(12+x) | | 2d^2=8-10d | | |x+1|=0 | | X=4.5+y | | 174=22x+8+6x-2 | | (3x^2+2x-6)+(x^2-4x)=x | | 60=7x+5 | | 4y^2+5y-12=0 | | 3 = q2 | | (-1)19= | | 7(2l+5)=91 | | (3x^2+2x-6)+(x^2-4x)= | | 4x^2+4x-9= | | d+3.77-1.99=5.38 |